Sejarah Melayu - Ahmad Dahlan, 1954- (Jakarta : Kepustakaan Populer Gramedia, 2014)
History of Malay people in Indonesia, Malaysia, and Singapore.
Includes bibliographical references (pages 597-602) and index.
In Indonesian.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Malaya -- History